(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
The study aims to evaluate the impact of dietary supplementation of different levels of black cumin seed on performance and carcass characteristics of Japanese quail. The study included six treatments, T0 (basal diet), T1 (basal diet + 0.5% black cumin seed), T2 (basal diet + 1.0% black cumin seed), T3 (basal diet + 1.5% black cumin seed), T4 (basal diet + 2.0% black cumin seed), and T5 (basal diet + 2.5% black cumin seed). The 450 experimental Japanese quails were then distributed to six treatments with five replications (15 birds/replication). The BW, BWG, FC, FCR, and DP of quail on different treatments was recorded. From the study, significant (p<0.05) differences were found in final FC among the dietary treatments. The final BWG also varied significantly (p<0.05) among the dietary treatments and significantly (p<0.05) higher BWG was observed in T3 and T4 groups. The improved FCR was observed with increasing of black cumin seed supplementation levels up to 2.0%. Moreover, significantly (p<0.05) higher DP was observed in T5 (2.5% black cumin seed) than other dietary treatments. Carcass characteristics revealed that significant (p<0.05) differences were observed for breast and wing weight but non- significant (p>0.05) differences were detected in back, thigh, neck, heart, liver, and gizzard weight among the dietary treatments. Moreover, significantly (p<0.05) lower abdominal fat was found in black cumin seed supplemented groups and highest result was found in T4 and T5. It is concluded that dietary supplementation of black cumin seed in quail ration significantly (p<0.05) improved the growth performance and carcass features of Japanese quail and the best result was obtained when supplemented with 1.5-2.0% black cumin seed. Therefore, it is recommended that the use of 1.5-2.0% black cumin in quail diet resulted in improved growth performance and carcass yields in Japanese quail. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 465-485